Tryptophan 2,3-dioxygenase may be a potential prognostic biomarker and immunotherapy target in cancer: A meta-analysis and bioinformatics analysis - Hu, Yanyan; Liu, Zhongjian; Tang, Hui (Frontiers in Oncology, 2022)
Background: Tryptophan2,3-dioxygenase (TDO2)is one of the emerging immune checkpoints. Meanwhile, TDO2 is also a key enzyme in the tryptophan (Trp)-kynurenine (Kyn) signalling pathway. Many researches have evaluated TDO2 is highly expressed in various malignant tumour patients and plays a prognostic role. However, the sample size of a single prognostic study was small, and the results were still controversial. Methods: We used Stata software and referenced the Preferred Reporting Items for Systematic Reviews and Meta-analysis (PRISMA) statement to conduct a meta-analysis on TDO2 and its clinical features and prognosis. We searched the PubMed, Cochrane Library, and Web of Science databases to find publications concerning TDO2 expression in malignant tumour patients up to June 2021. We used Newcastle–Ottawa Scale (NOS) to evaluate the bias risk of the included literature. Risk ratios (RRs) and hazard ratios (HRs) were used for clinical outcomes, specifically overall survival (OS) and progression-free survival (PFS). In addition, we used data from The Cancer Genome Atlas (TCGA) to verify our conclusions Results: Nine studies including 667 patients with malignant tumours were identified. Our results suggested that overexpression of TDO2 was statistically correlated with poor OS and poor PFS (HR = 2.58, 95% CI = 1.52–4.40, p=0.0005; HR = 2.38, 95% CI = 0.99–5.73, p=0.05). In terms of clinicopathological characteristics, overexpression level of TDO2 was statistically correlated with TNM (Tumor Node Metastasis) stage (RR = 0.65, 95% CI = 0.48–0.89, p = 0.002) and regional lymph nodes metastasis (RR = 0.76, 95% CI = 0.59–0.99, p = 0.04). Subgroup analysis revealed the potential sources of heterogeneity. In addition, bioinformatics studies suggested that level of TDO2 was high in malignant tumours and higher in cancer tissue than in matched paracarcinoma tissue. Gene enrichment analysis showed that TDO2 was closely related to immune response. Conclusion: Overall, TDO2 may be a biomarker for the survival and prognosis of patients with malignant tumours and a potential therapeutic target in the future. Systematic Review Registration: [https://www.crd.york.ac.uk/prospero/display_record.php?RecordID=260442] CRD42021260442